EVALUASI AKSEPTABILITAS TEKNOLOGI AI DALAM PERTANIAN BERKELANJUTAN DALAM KERANGKA SDGs 2 - Nurhayati (FAKULTAS TEKNIK, 2025)
Farming on large tracts of land in Indonesia is very difficult. This is because land is already being used for residential areas, which are increasing annually, and industrial development is increasing. Currently, the younger generation in Indonesia is not interested in agriculture, considering that agricultural yields are very low and do not guarantee a future. The existence of artificial intelligence (AI) technology and the assistance of IoT, a network of connected objects within AI, synergizes with each other, resulting in technological discoveries, especially in the agricultural sector, that can help reduce labor and agricultural failure due to natural conditions. This precision farming technology can make a strategic contribution to achieving SDG 2 (Zero Hunger) in the smallholder agricultural sector. This can be summarized in three main pillars: Productivity, Resilience, and Economic Inclusion. Precision farming technology can be formulated as a transformation of human profitability because it goes beyond achieving production figures to improving living standards.